Design of a High Gain Telescopic-Cascode Operational Amplifier Based on the ZTC Operation Condition - Kouhalvandi, Lida; Aygun, Sercan; Gunes, Ece Olcay; Kirci, Murvet (IEEE, 2017)
In recent years, telescopic cascode operational amplifiers have begun to be preferred due to their lower power consumption and higher bandwidths. In this paper, high-performance CMOS telescopic operational amplifier which has large DC gain and low power dissipation is presented. This telescopic cascode amplifier is based on the MOSFET zerotemperature coefficient (ZTC). In recent years, ZTC has been placed in the designs such as digital-to-analog converters, analog-to-digital converters, operational amplifiers, analog buffers, etc. The presented design is generated by combining two currents with a positive temperature coefficient and one with a negative temperature coefficient, in which an insensitive temperature current reference can be obtained. The operating temperature range from -30 degrees C to 80 degrees C is adjusted to ZTC current generator which provides stable and reliable operation throughout the desired temperature range. By using ZTC current reference as biasing, whole amplifier can be generated. The simple circuit and straightforward design structure make this approach advantageous over others. This circuit is verified by the simulation in Cadence 0.35 mu m CMOS technology. The power dissipation is kept low in mu W for the remote application and low sensitive to temperature. The simulated results show high gain of 82dB and phase margin 82 degrees at a load of 10pF while consuming 35.22 mu W power. Also, 15ns settling time shows the higher speed of the designed amplifier. This design uses MOSFET and other components such as BJT transistors and resistors.
Keywords: analog design; current generator; complementary-to-absolute-temperature; ICTAT; IPTAT; proportional-to-absolute-temperature; telescopic op-amp; temperature coefficient; ZTC; SC CIRCUITS; Engineering